The Implication of Halal Tourism Regulations to Encourage Community Well-Being: Lesson From Malaysia - Kusumaningtyas, Reza Octavia; Rodiyah, Rodiyah; Suprapti, Duhita Driyah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
It is crucial to ascertain whether halal tourism regulation can stimulate economic growth and promote sustainable national development to achieve community well-being. This research aims to advance halal tourism regulation to encourage the community's well-being. This research employs a qualitative methodology to conduct sociological and legal research. The research’s findings show that the decentralization of halal tourism regulation is intended to enhance the community's well-being. Nevertheless, the central level has not engaged in any discussions regarding the legal framework governing halal tourism implementation. The number of tourist visits, destinations, and hotels can be increased by the implications of halal tourism regulation in the form of Regional Regulations, particularly in West Nusa Tenggara. However, this has not resulted in community well-being. In contrast, Malaysia maintains robust institutions and regulations. The regulation of halal tourism in Malaysia is crucial for enhancing community well-being, as it promotes economic growth, employment opportunities, and adherence to Islamic principles. Consequently, it is crucial to enhance the institutional framework in Indonesia to supervise the implementation of halal tourism, foster collaboration among stakeholders, and strengthen regulations surrounding halal tourism to encourage community well-being.